The Hydrothermally synthesized hydroxyapatite from ale-ale shells as a bone graft material alternative - Tyas Galuh Amelia; Maulana Irfan Edri Prasetyo; Lalak Tarbiyatun Nasyin Maleiva; Adhityawarman; Syahrul Khairi (Jurnal Rekayasa Proses, 2026)
Ale-ale shells (Meretrix meretrix), a locally abundant shellfish waste in West Kalimantan, Indonesia, were investigated as a sustainable calcium precursor for the hydrothermal synthesis of hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂), the primary inorganic constituent of bone widely used in graft applications. Synthesis was conducted under varying reaction times (16–24 hours) and temperatures (140–180°C). FTIR and XRD analyses confirmed the formation of hexagonal-phase hydroxyapatite consistent with the JCPDS 09-0432 standard, with characteristic hydroxyl and phosphate functional groups detected and minor carbonate incorporation (1.00–1.52%), remaining well below the 8% limit for bone implant applications. The optimum condition was identified at 160°C for 20 hours, yielding nano-scale hydroxyapatite (14.50 nm) with high crystallinity (98.90%), satisfying ISO 13779 requirements. These findings highlight the potential of ale-ale shell-derived hydroxyapatite as a viable, locally sourced alternative to imported biomaterials while supporting the sustainable valorization of Indonesian shellfish waste.